Fizinę negalią turinčių jaunų asmenų užimtumas Lietuvoje: patirtys ir požiūriai - Braziene, Ruta; Zalkauskaite, Ugne (Socialiniai tyrimai, 2014)
The aim of this paper is to disclose the experiences and attitudes of young people with disabilities towards their professional activities and finding a job and to discover what the main opportunities and obstacles are for the integration of young disabled people into the Lithuanian labour market. The empirical basis of this research consists of 18 in-depth interviews with 18-35 year old young people with physical disabilities. In-depth interviews with young people with physical disabilities disclosed that a successful transition into the labour market first of all depends on the educational level (especially tertiary education) of a person, acquired appropriate employability skills, etc. Young disabled people experienced stigmatized attitudes by employers and a lack of interest to employ a disabled person. It is emphasized that employers in Lithuania are unwilling to employ a disabled person due to some special requirements (e.g., work assistant services, special requirements for the workplace, shorter working hours, etc.). In the high number of cases young people with disabilities face a double stigma, e.g., young and disabled, lack of working experience, etc.